2000
DOI: 10.1046/j.1365-2362.2000.00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum sialic acid and MMP‐9 with lipids and inflammatory markers

Abstract: Serum sialic acid does not appear to be an indicator of inflammation but is somehow connected with the level of total and HDL cholesterol. Serum matrix metalloproteinase-9 may provide a useful marker of inflammation because it correlates with the leukocyte count and is not associated with the lipid profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 33 publications
3
21
1
1
Order By: Relevance
“…Abdella et al [29] showed significant correlations between TSA concentrations and cardiovascular risk factors such as LDL cholesterol, triglycerides and apolipoprotein B in diabetic adults. Another study showed that TSA was significantly associated with lipid and lipoprotein concentrations in normal subjects [30]. In contrast, our findings showed no association between serum lipids and lipoproteins in our obese population aged 6–16 years.…”
Section: Discussioncontrasting
confidence: 97%
“…Abdella et al [29] showed significant correlations between TSA concentrations and cardiovascular risk factors such as LDL cholesterol, triglycerides and apolipoprotein B in diabetic adults. Another study showed that TSA was significantly associated with lipid and lipoprotein concentrations in normal subjects [30]. In contrast, our findings showed no association between serum lipids and lipoproteins in our obese population aged 6–16 years.…”
Section: Discussioncontrasting
confidence: 97%
“…In one report, baseline MMP-9 was associated with lower HDL cholesterol, 19 but no association of MMP-9 and HDL cholesterol was observed in another report. 28 A positive association of MMP-9 and WBC was observed in one report. 28 Additional studies need to be done on the epidemiological correlations of circulating MMP-9.…”
Section: Discussionmentioning
confidence: 82%
“…28 A positive association of MMP-9 and WBC was observed in one report. 28 Additional studies need to be done on the epidemiological correlations of circulating MMP-9.…”
Section: Discussionmentioning
confidence: 82%
“…13 Such a lack of correlation was equally observed for circulating levels of another metalloproteinase, MMP-9, in normolipidemic subjects apparently free of atherosclerosis 14 and in patients with premature coronary atherosclerosis. 15 Thus, the report of Bayes-Genis et al 9 and our present studies are concordant in identifying elevated serum PAPP-A levels as a marker of unstable or advanced hyper/isoechoic carotid atherosclerotic lesions, because early hypoechoic plaques are not associated with an elevation in circulating PAPP-A levels.…”
Section: Discussionmentioning
confidence: 97%